Thermogravimetric Analysis of Marine Macroalgae Waste Biomass as Bio-Renewable Fuel. (29th September 2022) - Khan, Nida; Sudhakar, K.; Mamat, R.
Abstract : Macroalgae are considered as the 3 rd generation of biofuels and a future feedstock for biorefinery. This research aims to provide simple and dependable analytical techniques for measuring the thermal characteristics of dried seaweed. The main objective was to investigate the thermal characteristics of four seaweed species utilizing a thermogravimetric analyzer. The seaweeds Gracilaria fisheri, Caulerpa lentillifera, Ceramium rubrum, and Eucheuma cottonii were collected from the Pahang state of Peninsular Malaysia. The calorific value of the samples was revealed by using a calorimeter. Ceramium rubrum showed the highest calorific value, while Gracilaria fisheri had the most negligible calorific value among the selected samples. The thermogravimetric analysis (TGA) data revealed that the most significant weight loss for this biomass occurred between 160 and 300° for the selected species. Gracilaria fisheri has shown the highest decomposition with the minor residue at 30.26%, whereas Caulerpa lentillifera has a slow weight loss rate in the mentioned range. SEM analysis has been used to perform the morphology of samples, which shows differences in the concentration of epiphytic diatoms with different structural shapes. Based on the results, macroalgae is a promising sustainable biomass feedstock for biofuel application.